2008
DOI: 10.1590/s0100-54052008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potato virus X on total phenol and alkaloid contents in Datura stramonium leaves

Abstract: RESUMOThe present paper reports results of the effect of Potato virus X (PVX) on the contents of total phenols and alkaloids in leaves of Datura stramonium. A significant decrease in the contents of phenols and alkaloids was observed in leaves inoculated with PVX (X-I). However, there was an increase in the percentage of phenols in leaves rubbed with phosphate buffer (C1-I) and in leaves from the nodes immediately above, possibly induced by mechanical injury. Gas chromatography/mass spectroscopy revealed amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
2
9
1
4
Order By: Relevance
“…It was well expressed in the reduction in the phytochemcial contents of saponins, alkaloids, terpenoids, reducing sugars and steroids. Reductions engendered by MWMV infection are in agreement with previous reports by El-Dougdoug et al (2007), Duarte et al (2008) and Mofunanya and Nta (2011). Significant increases in glycosides and flavonoids and insignificant increase in tannins in infected samples reported in this study are in line with findings by Uegaki et al (1998), who reported on the accumulation of stress compounds due to virus infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was well expressed in the reduction in the phytochemcial contents of saponins, alkaloids, terpenoids, reducing sugars and steroids. Reductions engendered by MWMV infection are in agreement with previous reports by El-Dougdoug et al (2007), Duarte et al (2008) and Mofunanya and Nta (2011). Significant increases in glycosides and flavonoids and insignificant increase in tannins in infected samples reported in this study are in line with findings by Uegaki et al (1998), who reported on the accumulation of stress compounds due to virus infection.…”
Section: Discussionsupporting
confidence: 93%
“…El-Dougdoug et al (2007) reported that PVY infection led to a decrease in total alkaloids contents in leaves of Datura metel. Duarte et al (2008) also reported a decrease in total phenol and alkaloids content in the same plant inoculated with PVX. Report by Rangaraju and Chenulu (1975) revealed that mosaic virus reduces the fruit content of solasonin (a medically useful alkaloids) to about half.…”
Section: Introductionmentioning
confidence: 82%
“…By using certain modifiers/ spreaders and micropropogating the plants of B. diffusa on suitable modified MS medium, the antiviral activity has been markedly improved and prolonged. Thus, a modest beginning towards successful virus control has been made [236][237][238][239][240][241][242]. …”
Section: Ecofriendly Managementmentioning
confidence: 99%
“…The fourth and fifth leaves above the cotyledonaries of the C 2 group were rubbed with 50 lL of inoculation buffer. Leaves of PVY O group at the same position as those from C 2 group were treated with 50 lL of the virus inoculum (Duarte et al 2008).…”
Section: Experimental Designmentioning
confidence: 99%
“…These metabolic changes can still be different in the local of infection or systemically (Krečič-Stres et al 2005;Choi et al 2006;Duarte et al 2008) and depending on the resistance of the plant to a specific pathogen (Krečič-Stres et al 2005).…”
Section: Introductionmentioning
confidence: 99%